COVID-19 and migrants: lessons for pandemic preparedness from the Malaysian experience - Sharuna Verghis (BMC, 2023)
Abstract Background Aligning with global evidence related to migrants and COVID-19, the pandemic highlighted and exposed long-standing structural inequities in the context of migrant populations in Malaysia who experienced a disproportionate level of exposure to SARS-CoV-2 and COVID-19 morbidity, as well as exacerbated precarity during COVID-19 owing to disruptions to their livelihoods, health, and life. Main body Focusing on COVID-19 and migrant workers in Malaysia, this review addresses two research queries: (i) what are the policy responses of the government toward migrants with regard to COVID-19? (ii) what are the lessons learned from the Malaysian experience of COVID-19 and migrants that can inform pandemic preparedness, especially regarding migrant health policy? The review used Arksey and O'Malley's methodological framework refined by Levac, Colquhoun, and O'Brien. In addition to the PubMed, Web of Science, Scopus, and EBSCO databases, and Malaysian English language newspapers, including the Malay Mail, Malaysiakini, and the New Straits Times, the search also included reports from the websites of government ministries and departments, such as the Immigration Department, Ministry of Human Resources, Ministry of Health, and the International Trade and Industry Ministry. Conclusion Using the case example of Malaysia and the policy approach toward migrant populations in Malaysia during the height of the COVID pandemic in 2020 and 2021, this paper unravels complex pathways and inter-linkages between the contexts of migration and health which coalesced to engender and exacerbate vulnerability to disease and ill-health for the migrant workers. The lack of coordination and coherence in policies addressing migrant workers during the pandemic, the normalization of cheap and disposable labor in neoliberal economic regimes, and the securitization of migration were key factors contributing to the failure of migration policies to provide protection to migrant workers during COVID-19. The review suggests that policy approaches embodying the principles of Health in All Policies, a whole-of-society approach, and the promotion of safe, just, and regular migration, predicated on equity and inclusion, are integral to a comprehensive and effective response to pandemics such as COVID-19.